Prevalance of Renal and Electrolyte Disorders in Chronic Heart Failure Patients - Naveed Yaqoob, Muhammad Ahmad Raza Butt, Faiza Nafees Khan, Muhammad Ilyas, Muhammad Haidar Zaman, Fahad Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To determine the prevalence of renal and electrolyte disorders in patients presented with chronic heart failure. Study Design: Cross sectional/Observational Place & Duration of Study: Data was collected from the different tertiary care hospitals of Pakistan, including Rawal Institute of Health Sciences, Islamabad and Department of Cardiology, Rashid Latif Medical College, Lahore During the period from January, 2022 to June, 2022. Methods: Total 210 patients of both genders with ages 25 to 75 years presented with chronic heart failure were analyzed. Patients detailed demographic were recorded after taking written consent. Blood samples of all the patients were collected to examine the serum electrolyte and serum creatinine. Prevalence of renal dysfunction and electrolyte disorders were recorded.ae Results: One hundred and fifty two (72.38%) patients were males while 58 (27.62%) patients were females. 85 (40.48%) patients were ages 25 to 50 years and 125 (59.52%) were ages between 51 to 75 years. Renal dysfunction was found in 61 (29.05%) patients, 56 (26.67%) patients had hypokalemia and hyponatremia was found in 59 (28.10%) patients. Conclusion: The incidence of renal dysfunction and electrolyte disorders in patients with chronic heart failure was high. Patients with ages above 50 years had high rate of renal dysfunction, hypokalemia and hyponatremia. Keywords: Chronic Heart Failure, Renal Dysfunction, Hyponatremia, Hypokalemia